The action representation elicited by different types of drug-related cues in heroin-abstinent individuals - Zeng, Hong; Vollstädt-Klein, Sabine (Frontiers in behavioral neuroscience, 2018)
Drug related cue-induced reactivity plays a significant role in maintaining drug use and relapse in addicted individuals. The activation of dorsal lateral striatum -sensorimotor system (DLS-SM) has been suggested as an important route through which drug cues may induce automatic drug using behavior. The current study used fMRI to investigate the reactivity of heroin abstinent individuals to different types of cues, to clarify the characteristics of the cues that induce the activation of the sensorimotor area. 40 heroin-dependent abstinent individuals and 29 healthy subjects were recruited to perform the heroin cue-reactivity task during fMRI. The participants’ subjective craving and physical signs were evaluated before and after scanning. Whole-brain analysis showed that compared to drug use tool and drug cues, cues related to drug use action were more likely to activate bilateral middle temporal cortex, bilateral calcarine and bilateral inferior parietal cortex. Left insula, bilateral caudate and right putamen were signiﬁcantly activated in neural interactions among subjects group, cue category and cue type. These areas are involved in motor preparation and output, indicating that the DLS-SM area is also an important neural basis of craving and automatic drug using behavior, and may mediate craving and drug seeking behavior. Our findings thus suggest that cues related to drug using action may induce automatic drug seeking behavior more than cues related only to the drug itself.
Gesehen am 14.12.2020